(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Continuous professional practice of students is important in improving their professional training and ensuring their competitiveness in the labor market. Effective organization and management of this process creates opportunities for students to gain practical experience. Foreign experiences show what factors play an important role in this process. Foreign experiences show that it is necessary to clearly define the purpose of professional practice. For example, in Germany, there is a dual education system, in which students are actively involved in practice, along with acquiring theoretical knowledge.